Mutational Analysis at Intersubunit Interfaces of an Anionic Glutamate Receptor Reveals a Key Interaction Important for Channel Gating by Ivermectin - Degani-Katzav, Nurit; Gortler, Revital; Weissman, Marina; Paas, Yoav (Frontiers in Molecular Neuroscience, 2017)
The broad-spectrum anthelmintic drug ivermectin activates and stabilizes an open-channel conformation of invertebrate chloride-selective glutamate receptors (GluClRs), thereby causing continuous inflow of chloride ions and sustained membrane hyperpolarization. These effects suppress nervous impulses and vital physiological processes in parasitic nematodes. The GluClRs are pentamers. Homopentameric receptors assembled from the Caenorhabditis elegans GluClα (GLC-1) subunit can inherently respond to ivermectin but not to glutamate (the neurotransmitter). In contrast, heteromeric GluClα/β (GLC-1/GLC-2) assemblies respond to both ligands, independently of each other. Glutamate and ivermectin bind at the interface between adjacent subunits, far away from each other; glutamate in the extracellular ligand-binding domain, and ivermectin in the ion-channel pore periphery. To understand the importance of putative intersubunit contacts located outside the glutamate and ivermectin binding sites, we introduced mutations at intersubunit interfaces, between these two binding-site types. Then, we determined the effect of these mutations on the activation of the heteromeric mutant receptors by glutamate and ivermectin. Amongst these mutations, we characterized an α-subunit point mutation located close to the putative ivermectin-binding pocket, in the extracellular end of the first transmembrane helix (M1). This mutation (αF276A) moderately reduced the sensitivity of the heteromeric GluClαF276A/βWT receptor to glutamate, and slightly decreased the receptor subunits’ cooperativity in response to glutamate. In contrast, the αF276A mutation drastically reduced the sensitivity of the receptor to ivermectin and significantly increased the receptor subunits’ cooperativity in response to ivermectin. We suggest that this mutation reduces the efficacy of channel gating, and impairs the integrity of the ivermectin-binding pocket, likely by disrupting important interactions between the tip of M1 and the M2‑M3 loop of an adjacent subunit. We hypothesize that this physical contact between M1 and the M2-M3 loop tunes the relative orientation of the ion-channel transmembrane helices M1, M2 and M3 to optimize pore opening. Interestingly, pre-exposure of the GluClαF276A/αWT mutant receptor to subthreshold ivermectin concentration recovered the receptor sensitivity to glutamate. We infer that ivermectin likely retained its positive modulation activity by constraining the transmembrane helices in a preopen orientation sensitive to glutamate, with no need for the aforementioned disrupted interactions between M1 and the M2-M3 loop.